“EU MANE GIR HI’ANG” : Model Pengentasan KDRT Dengan Pendekatan Inovasi Berbasis Kearifan Lokal di Provinsi NTT - Maria Fransiska Amu Oyan; Indriyati Indriyati (STISIPOL Raja Haji, 2026)
Violence against women is a complex social problem and remains a significant challenge in Indonesia, including in East Nusa Tenggara Province. The main factors hindering the effective handling of this problem are economic dependence on the perpetrator and the strong culture that views domestic violence as a private matter. This study aims to describe and analyze the implementation of the innovative program